"I Wouldn't Want to Operate without It": The Ethical Challenges Faced by Experienced Sport Psychology Consultant's and Their Engagement with Supervision. Issue 3 (4th May 2021) - Sharp, Lee-Ann; Hodge, Ken; Danish, Steven
Abstract : The aims of this investigation were to; (a) explore the ethical challenges that sport psychology consultants (SPCs) have experienced in their applied practice, and (b) examine the engagement of SPCs with monitoring and supervision of their applied practice. Ten experienced SPCs participated in individual interviews. Following content analysis, two categories of ethical challenges faced by SPCs emerged: (a) challenges to boundaries and (b) communication issues. Four subcategories emerged in relation to SPC engagement in the supervision of their practice: (a) supervision is essential, (b) supervision enabled SPCs to monitor boundaries, (c) supervision helped SPCs to feel supported, and (d) supervision aided SPCs to get to know themselves and care for themselves. Lay summary: This investigation aimed to explore the ethical challenges that sport psychology consultants (SPCs) have experienced in their applied practice in elite sport and to examine the engagement of experienced SPCs with monitoring and supervision of their applied practice. Results highlighted that SPCs faced challenges to boundaries and communication issues in their applied practice. While highlighting that supervision was an essential component of applied practice that enabled SPCs to monitor boundaries of applied practice, aided SPCs to get to know themselves and care for themselves, feeling supported in their applied practice at the same time.